ACE INHIBITORS AND ARBS INFLUENCE ON MOBILITY OUTCOMES IN OLDER ADULTS: RESULTS FROM THE LIFE TRIAL. (16th November 2018) - Brown, J; Kritchevsky, S; Buford, T; Gill, T; Strotmeyer, E; Smith, S; Pahor, M; Manini, T
Abstract: Angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARBs), generally considered interchangeable in cardiovascular disease, are thought to preserve mobility throughout aging. Whether these drug classes exert differential effects on aging-related outcomes is unknown. Distinguishing unique effects could inform prescribing practices and uncover underlying mechanisms for these effects. The purpose of this study was to compare ACEis and ARBs based on their association with mobility disability in a secondary analysis of the Lifestyle Interventions for Elders (LIFE) trial. Participants aged 70–89 years, who were sedentary with existing physical limitations, were randomized to a physical activity intervention or a health education control arm and longitudinally assessed for incident and persistent major mobility disability (MMD), serious falls, Short Physical Performance Battery, and gait speed. Participants were divided into ACEi and ARB medication groups. Outcomes were compared between ACEi and ARB groups with propensity score weighted proportional hazards and ANCOVA models. Of 1, 635 participants in the LIFE study, 796 used either ACEi (496, 62.3%) or ARBs (300, 37.7%). Compared to ACEi users, ARB users had a 28% reduction (HR=0.72 [0.60–0.85]) for incident MMD and a 35% (HR=0.65 [0.52–0.82]) reduction for persistent MMD, which was independent of treatment arm assignment. Risks of other outcome measures were not different between ARB and ACEi users. Given the LIFE trial was not specifically powered to detect subgroup differences, these results strengthen the case for preferential use of ARBs in older adults but warrant further research to confirm this effect.